Assessment of antibacterial potential of Natural and Commercial Honey samples against Wound Isolates - Fatima, Zareen; Zafar, Sidra; Batool, Tuba (International Journal of Endorsing Health Science Research, 2020)
Background: Antibiotic resistance has surged the development and exploration of new, improved and effective natural products from plants and other sources like Honey has been rediscovered as a therapy for wounds, both in-vitro studies and in clinical trials. It has been observed to exert bacteriostatic and bactericidal potentials against pathogenic bacteria, including drug-resistant strains. The following study aimed to isolate and identify bacteria from wound infections and to investigate the antibacterial activity of honey samples; natural and commercial honey, against common clinical wound Pathogens. Methodology: Bacteria from wound samples of patients with injured legs were isolated using differential and selective agars, while the antibacterial activity of natural and commercial honey samples was determined by agar well diffusion method and minimum inhibitory concentrations (MIC). Results: The results indicated that natural honey has more potential to exert antibacterial activity with an 18-30mm zone of inhibition, which was significantly higher as compared to commercial honey with a 13-23mm zone of inhibition. MIC of natural honey was visible in most of the test organisms at25µg/ml as compared to commercial honey with only Bacillus sp and Staphylococcus sp2 at 50 µg/ml while Staphylococcus sp1 at 25µg/ml. Conclusion: The results propose due to a significant difference in the antibacterial activity of natural and commercial honey, these findings would help experts from the health sciences in the selection of the type of honey as an apitherapy for wound care and management.